The Role of Physical Activity in Menopausal Women - Amansyah, Adek; Naurah Al’Ariqoh; Meldawati (HM Publisher, 2024)
Menopause is the permanent cessation of the menstrual cycle due to decreased ovarian function, resulting in a decrease in follicles. A person is said to be experiencing menopause if they do not experience menstruation for 12 months. Symptoms that occur during menopause include somatic, psychological, and urogenital symptoms. Exercise has many benefits for body health. Exercise, such as regular physical activity, is considered to reduce complaints during menopause. This study aims to identify the relationship between various physical activities and menopausal symptoms in women aged 50-60 years in the working area of the Ujunggading Health Center. This research uses a correlation research design with a cross-sectional approach model with a sample size of 75 respondents using the nonprobability sampling method, namely using purposive sampling, data collection using GPAQ and MRS questionnaires, and data analysis using correlation tests. The results of the research from 75 respondents showed that the frequency distribution of the characteristics of respondents with the highest occupation was as a housewife, namely 23 people (30.7%), the highest education was junior high school, namely 20 people (26.7%), and the highest duration of menopause was 5-7 years, namely 36 people (48.0%). Shows that many respondents have physical activity in the moderate category 54 (72%), and many respondents experience menopausal symptoms in the moderate category 37 (49.3%). There is a relationship between physical activity and menopausal symptoms with a p-value = 0.000 (p<0.05). There is a relationship between physical activity and menopausal symptoms where the higher the physical activity carried out, the less menopausal symptoms are felt, menopausal symptoms can be reduced by routinely doing activities and exercising for 15 to 60 minutes every day.